Pengaruh Persepsi Dan Preferensi Konsumen Terhadap Keputusan Pembelian Rumah Tipe Premium (Studi Pada Konsumen Kawanua Emerald City Akrland Manado - Lolowang, Isye R (Universitas Sam Ratulangi, 2019)
The purpose of this study was determine to the effect of perception and consumer preferences On Premium Type Purchase Decisions (Study On Consumers Kawanua Emerald City AkrLand Manado. This research used quantitative research models of associative. The results of this study are that consumer perceptions and preferences have a significant effect on purchasing decisions simultaneously. Consumer perception has no significant effect on purchasing decisions partially. Consumer preference has a significant effect on purchasing decisions partiallyKeywords: Perception, consumer preferences, purchasing decisions